Challenges and opportunities for recycling excreta for peri-urban agriculture in urbanising countries - Cofie, Olufunke O.; Rooijen, Daniel J. van; Nikiema, Josiane (2014)
As urbanisation increases, so does the challenge of meeting water, sanitation and food requirements in urban areas. In particular, the management of human excreta from on-site sanitation facilities remains a challenge and continues to endanger public health and degrades the environment through soil and water pollution. Yet much of the excreta consist of organic matter and nutrients that are valuable inputs for agriculture. Recycling in agriculture has often neglected the recovery of nutrients and organic matter in faecal sludge collected from on-site sanitation facilities in developing countries. Exploring the high proportion of resources in excreta can provide a win–win strategy by reducing the environmental pollution, enhancing soil fertility and therefore improving livelihoods. Challenges to maximising these benefits include: type of sanitation facility used in developing countries, nature of faecal materials, prevailing treatment technologies which are usually designed for waste disposal not for reuse, institutional and market factors as well as negative perceptions regarding excreta use in agriculture. Nevertheless, urban and peri-urban agriculture presents a good opportunity for nutrient recycling, provided that technological and socio-economic strategies for optimum recovery are taken into account. The paper concludes with a description of successful recycling options that can contribute to improving farm productivity, using evidence from Ghana.